1985
DOI: 10.1288/00005537-198504000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngologic and head and neck manifestations of acquired immunodeficiency syndrome (AIDS).

Abstract: Patients with acquired immune deficiency syndrome (AIDS) frequently present with signs and symptoms referable to the head and neck. Three hundred ninety-nine patients with AIDS presented at the University of California, San Francisco and its affiliated hospitals from 1980 to April 1984. One hundred sixty-five patients (41%) with AIDS presented with, or had on initial evaluation, head and neck manifestations. Of that group, 58 (35%) had cutaneous, oral, and pharyngeal lesions of Kaposi's sarcoma; 51 (31%) had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(37 citation statements)
references
References 5 publications
4
30
0
3
Order By: Relevance
“…1 Head and neck disease is amongst the most commonly reported manifestation of HIV/AIDS, and has been documented since the discovery of HIV in the early 1980s. 2,3 The incidence of head and neck related symptoms of HIV/AIDS has been reported to vary between 40 and 90 per cent. [4][5][6][7] Many of these symptoms are characterised by involvement of the auditory system, as a result of the direct effect of HIV infection, or indirectly due to a combination of opportunistic infections or associated ototoxic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…1 Head and neck disease is amongst the most commonly reported manifestation of HIV/AIDS, and has been documented since the discovery of HIV in the early 1980s. 2,3 The incidence of head and neck related symptoms of HIV/AIDS has been reported to vary between 40 and 90 per cent. [4][5][6][7] Many of these symptoms are characterised by involvement of the auditory system, as a result of the direct effect of HIV infection, or indirectly due to a combination of opportunistic infections or associated ototoxic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, miscellaneous pathological changes that are closely related to this retroviral infection or to its various complications have been reported (1,2). Among these, a somewhat underrecognized and intriguing feature is the occasional presence of multinucleated giant cells (MGCs) in hyperplastic lymphoid tissue of the WR (2-10).…”
mentioning
confidence: 99%
“…Similar studies in the USA, Spain and Brazil identified oropharyngeal candidiasis and kaposis sarcoma as the commonest primary manifestations of HIV/AIDS in the head and neck region. [20][21][22] This is at variant with our finding of chronic tonsillitis as the commonest ENTH&N condition that is associated with HIV infection.…”
Section: Discussionmentioning
confidence: 74%